2020
DOI: 10.1002/bit.27512
|View full text |Cite
|
Sign up to set email alerts
|

Combining model structure identification and hybrid modelling for photo‐production process predictive simulation and optimisation

Abstract: Integrating physical knowledge and machine learning is a critical aspect of developing industrially focused digital twins for monitoring, optimisation, and design of microalgal and cyanobacterial photo-production processes. However, identifying the correct model structure to quantify the complex biological mechanism poses a severe challenge for the construction of kinetic models, while the lack of data due to the time-consuming experiments greatly impedes applications of most data-driven models. This study pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Hybrid modeling applications in the biopharma sector are currently boosting particularly for Process analytical technology (PAT) [13,[73][74][75] and quality by design (QbD) [7,34,35,45] . Industry 4.0 [13,76] , big data [13,77] , and digital twin [47,78] are recently added subjects that introduce new concepts that challenge the application of hybrid modeling to the digitalization of biopharmaceutical processes. A report from an expert panel discussion of European academics and industrialists has addressed the drivers, challenges, and enablers of hybrid modeling applications in the biopharmaceutical industry [45] .…”
Section: Research Gapmentioning
confidence: 99%
“…Hybrid modeling applications in the biopharma sector are currently boosting particularly for Process analytical technology (PAT) [13,[73][74][75] and quality by design (QbD) [7,34,35,45] . Industry 4.0 [13,76] , big data [13,77] , and digital twin [47,78] are recently added subjects that introduce new concepts that challenge the application of hybrid modeling to the digitalization of biopharmaceutical processes. A report from an expert panel discussion of European academics and industrialists has addressed the drivers, challenges, and enablers of hybrid modeling applications in the biopharmaceutical industry [45] .…”
Section: Research Gapmentioning
confidence: 99%
“…Bioprocesses often exhibit high variability due to their complex underlying process mechanisms. With the involvement of multiple phases (gas, liquid, and solid), the underlying process can behave in an unpredictable way over a broad range of time and length scales (Zhang et al, 2020). As a result, developing an accurate process model with high reliability (i.e., low uncertainty) is particularly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The black‐box and white‐box modules can be arranged in three different ways, that is, parallel to each other or one of the two serial structures depending on their order (von Stosch et al, 2014), as shown in Figure 3. In parallel structure, the black box model can map the residuals between experimental and white box model predictions so that mechanistic model outputs can be corrected for future prediction (Bhutani et al, 2006) or to account for the unknown dynamics in numerical integration (Zhang et al, 2020). Very similar framework with some differences in objective, ML algorithm has been adopted in different studies (see Table 1).…”
Section: Hybrid Model Structural Frameworkmentioning
confidence: 99%